Distinguishing computable mixtures of quantum states - López Grande, Ignacio Hernán (2018)
In this article we extend results from our previous work [Bendersky, Phys. Rev. Lett. 116, 230402 (2016)PRLTAO0031-900710.1103/PhysRevLett.116.230402] by providing a protocol to distinguish in finite time and with arbitrarily high success probability any algorithmic mixture of pure states from the maximally mixed state. Moreover, we include an experimental realization, using a modified quantum key distribution setup, where two different random sequences of pure states are prepared; these sequences are indistinguishable according to quantum mechanics, but they become distinguishable when randomness is replaced with pseudorandomness within the experimental preparation process.